The Green Revolution in Gili Balu: Policy Convergence, Blue Economy, and Community Empowerment - Jalaluddin Jalaluddin; Hayati Hayati (Jurnal Biologi Tropis, 2026)
The Green Revolution has become a prominent policy framework for promoting sustainable development in Indonesia’s marine and fisheries sector. However, its implementation in small island regions often reveals a significant gap between policy objectives and local socio-ecological realities. This study aims to critically examine the convergence and tensions among the Green Revolution as a policy framework, the Blue Economy as a development model, and community empowerment as the ultimate goal of sustainable development in small island contexts. Using a qualitative approach, this study employs a Critical Narrative Review of 13 selected articles and policy documents, complemented by contextual reflections on Gili Balu, a small island cluster in West Sumbawa Regency, Indonesia. The analysis identifies three dominant themes: technocratic development approaches, community-based Blue Economy practices, and participatory empowerment. The findings indicate that while these concepts are theoretically complementary, their implementation is often constrained by weak local institutions, limited community authority, fragmented policy integration, and unequal access to resources. In Gili Balu, locally driven initiatives such as community-based tourism and marine resource conservation demonstrate the potential of adaptive and inclusive governance. The study concludes that sustainable transformation in small islands requires stronger integration between policy frameworks, local institutions, and community participation. The novelty of this study lies in its integrated analytical framework that connects Green Revolution, Blue Economy, and community empowerment to explain the dynamics of sustainable development in small island regions.